2022
DOI: 10.1177/17427150221083784
|View full text |Cite
|
Sign up to set email alerts
|

Paternalistic leadership as a double-edged sword: Analysis of the Sri Lankan President’s response to the COVID-19 crisis

Abstract: Despite the challenges facing small economies, leadership research has given scant attention to leaders’ behaviour in those countries during crises. Using seemingly paradoxical domains of paternalistic leadership theory: authoritarian, benevolent and moral leader behaviour, together with concepts like populism from the political science domain, we analyse how Sri Lanka’s ‘strongman’ President provided a façade of paternalistic leadership during the first phase of the COVID-19 pandemic. Through analysis of writ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…H5 is also rejected because a paternal leader is not allowed to influence employee job retention (Gyamerah et al 2022) when he or she is not fulfilling the requirement of a business environment, especially when the employee needs leader attention and support and the leader is not available for them and preferring there business goals and objectives instead of their employees' needs. The results indicated that the V-HRM (Mondejar and Asio 2022) consistency strengthens two relationships-empowerment trait-work engagement and empowerment trait of paternal leaders (Gunasekara et al 2022) and employee job retention (Sheridan 1992), respectively (H7).…”
Section: Discussionmentioning
confidence: 90%
“…H5 is also rejected because a paternal leader is not allowed to influence employee job retention (Gyamerah et al 2022) when he or she is not fulfilling the requirement of a business environment, especially when the employee needs leader attention and support and the leader is not available for them and preferring there business goals and objectives instead of their employees' needs. The results indicated that the V-HRM (Mondejar and Asio 2022) consistency strengthens two relationships-empowerment trait-work engagement and empowerment trait of paternal leaders (Gunasekara et al 2022) and employee job retention (Sheridan 1992), respectively (H7).…”
Section: Discussionmentioning
confidence: 90%
“…Power exercised through authoritarian behavior, in contrast to authoritative behavior, together with promoted morality and kindness, seems to be effective in the short term in dealing with the pandemic (Gunasekara et al, 2022).…”
Section: Implementation Of Patentarlistic Leadershipmentioning
confidence: 98%
“…Leadership researchers in Asia, using a grounded (emic) approach, have identified a common array of behaviors used by managers that has been called paternalistic leadership [38,39]. Paternalistic leadership is rooted in the traditional Chinese philosophy of Confucianism [40][41][42] and is commonly found in collectivistic and high-power-distance cultures in Asia, like Sri Lanka [43]. Takeuchi, Wang, and Farh [44] argue for the potential for Asian conceptualizations of leadership building on the paternalistic leadership style.…”
Section: Paternal Leadershipmentioning
confidence: 99%